PENGARUH TERAPI MUROTTAL AL-QUR’AN SURAH AR-RAHMAN TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI PSTW BUDI LUHUR KOTA JAMBI - Agus Susilawati (Universitas Baiturrahim, 2019)
Hypertension is a condition where a person experiences an increase in blood pressure above normal which is indicated by a figure of 140 mmHg systolic and 90 mmHg diastolic. One of the management of non-pharmacological hypertension is the therapy of murottal Al-Qur'an Surah Ar-Rahman. This study aimed to determine the effect of therapeutic Murottal Al-Qur'an Surah Ar-Rahman toward decreased blood pressure in elderly hypertensive patients in PSTW Budi Luhur Jambi City. This study was conducted on April 9th-20th 2019 with total samples were 16 people. Sample used purposive sampling technique. The instrument used sphygmomanometer digital and observation sheet. After being given the intervention of therapeutic Murottal Al-Qur’an, the mean value of systole blood pressure was obtained 157 mmHg, on the statistical test was obtained score p-value 0,000 (˂0,05), the mean value of diastole blood pressure after intervention is 88,19 mmHg, on the statistical tests was obtained score p-value 0,000 (˂0,05) it means there is the effect of therapeutic Murottal Al-Qur'an Surah Ar-Rahman toward decreased blood pressure in elderly hypertensive patients in PSTW Budi Luhur Jambi City. It is conclused that respondents who were given therapeutic murottal Al-Qur'an experienced a decrease in blood pressure. It is expected to PSTW Budi Luhur Jambi City to applying non-pharmacological therapies such as the therapeutic Murottal Al-Qur'an Surah Ar-Rahman to reduce blood pressure in elderly people with hypertension.